Método de obtenção das magnetizações de blocos magnéticos de NdFeB a partir de perfís de curvas de integral de campo magnético - Santo, Gustavo Correia Espirito (Universidade Federal de São Carlos, 2022)
Synchrotron light is a type of electromagnetic radiation emitted when relativistic charged particles are subjected to an acceleration perpendicular to their velocity, such as the acceleration created by the force of a magnetic field. When passing through a magnetic field, the particle undergoes a deflection in its trajectory, causing synchrotron radiation to be emitted in the tangent direction of its path. It is extremely bright and spans a wide spectrum, allowing different types of analysis to be performed with the different radiations that compose it. The main equipment responsible for producing this type of radiation are called Insertion Devices (ID). Consisting of a set of dipoles with alternating polarity, these devices cause oscillations in the path of electrons, causing them to emit radiation. An extremely important figure of merit for IDs is the field integral, which effectively represent the effects caused by a magnetic field on charged particles. In this way, the field integrals provide the angular and positional deviations of the output electron path with respect to the input path in the insertion devices. Magnetic simulations are used in order to describe and predict such parameters. However, to carry out the simulations, it is necessary to know precisely the geometric and magnetic parameters involved in such a process. Thus, the present work intends to present a method for determining the magnetization components of magnetic blocks used in insertion devices, from field integral curve profiles, allowing to reliably predict the various magnetic parameters that involve accelerator physics, through the magnetic simulations. This method was tested and validated, managing to satisfactorily describe the effects for a set of periodically arranged blocks, called subcassette, simulating the magnetic field and field integral curves, obtaining differences < 50 G.cm.
Method of obtaining block magnetizations NdFeB magnets from field integral curve profiles
Keywords: Dispositivos de inserção; Luz síncrotron; Campo magnético; Dipolos magnéticos; Simulação magnética; Integrais de campo; CIENCIAS EXATAS E DA TERRA::FISICA